2020
DOI: 10.1002/ece3.5960
|View full text |Cite
|
Sign up to set email alerts
|

Communicating the consensus on climate change to college biology majors: The importance of preaching to the choir

Abstract: College and university biology majors who are not climate change deniers may yet be unaware of the degree of scientific consensus on climate change and unprepared to communicate about climate science to others. This study reports on a population of climate change accepting biology majors at a large, private research university in the American northeast. Our students tended to greatly underestimate the degree of scientific consensus around climate change, to be only moderately worried about climate change, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Finally, our participants' increased knowledge about the scientific consensus on GM food and vaccination could have motivated them to discuss it with their peers. It has been shown that the more people know about the scientific consensus on global warming, the more likely they are to discuss it with their peers, leading to a "proclimate social feedback loop" [Goldberg et al, 2019, p. 1; see also Sloane and Wiles, 2020]. Even though the present study did not measure participants' sharing behaviors after the experiment, we strongly encourage future research to do so as it is an important -alas neglected -dimension of science communication.…”
Section: Limitationsmentioning
confidence: 99%
“…Finally, our participants' increased knowledge about the scientific consensus on GM food and vaccination could have motivated them to discuss it with their peers. It has been shown that the more people know about the scientific consensus on global warming, the more likely they are to discuss it with their peers, leading to a "proclimate social feedback loop" [Goldberg et al, 2019, p. 1; see also Sloane and Wiles, 2020]. Even though the present study did not measure participants' sharing behaviors after the experiment, we strongly encourage future research to do so as it is an important -alas neglected -dimension of science communication.…”
Section: Limitationsmentioning
confidence: 99%
“…These results suggest that the chatbot could play a useful role beyond providing information to those directly exposed to it, as people use and share the chatbot to others (as in 2-step and multistep flow models of communication, see, e.g., Ahn et al, 2014; Katz & Lazarsfeld, 1955). More generally, the role of interpersonal communication in the dissemination of reliable information is being increasingly recognized in the field of risk communication (see, e.g., Altay & Lakhlifi, 2020; Altay & Mercier, 2020; Goldberg et al, 2019; Sloane & Wiles, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…There is apparently no previous work investigating association between pre-service coursework and perception of scientific consensus on evolution, except insofar as studies such as Rutledge and Mitchell (2002) and Toro (2018) are regarded as doing so: as Sickel and Friedrichsen (2013) note, instruments purported to assess personal acceptance of evolution often seem to be assessing perception of scientific acceptance of evolution (see also Tourangeau et al 2016). A substantial body of work on scientific consensus on climate change suggests that awareness of scientific consensus is significantly associated with acceptance and thus predictive of appropriate action (see, e.g., Sloane and Wiles 2020;van der Linden et al 2015; van der Linden 2021). In the case of high school biology teachers, it might be expected that awareness of the scientific consensus on evolution would Branch et al Evolution: Education and Outreach 2023, 16(1):4 similarly be predictive of desirable classroom outcomes, so the association between pre-service coursework and awareness of the scientific consensus is of interest.…”
Section: Perception Of Scientific Consensus On Evolutionmentioning
confidence: 99%